Simulation of controlled systems with nonlinear quality regulators - Глазок, О. М. (Proceedings of National Aviation University (archive), 2021)
The outcomes of applying the new method of synthesis of regulators for nonlinear dynamic objects are investigated. The task of synthesis is solved by the updated method of analytical constructing on the basis of a square-law functional of quality. The application of a method of simulation is considered at research of quality of the controlled systems obtained as a result of synthesis.